THE INFLUENCE OF DIGITAL CULTURE IN BUSINESS MODEL CHANGE IN ECONOMY 5.0 - Loso Judijanto (Jurnal Salome : Multidisipliner Keilmuan, 2025)
The influence of digital culture on business model change in the era of Economy 5.0 is significant, driven by the adoption of advanced technologies such as artificial intelligence, the Internet of Things (IoT), and big data analytics. This technological transformation enables companies to optimise operations and deliver more value to customers, requiring them to be more flexible and adaptive to market changes. The shift in focus from products to services, known as 'servitization', and the dominance of platform-based business models mark a major shift in business models. In addition, digital culture is driving the renewal of organisational structures to become flatter and more collaborative, and demands increased skills and innovation. The integration of this digital culture strengthens companies' efficiency and ability to deliver a more personalised customer experience, and maintain competitiveness in an increasingly competitive global marketplace.